Management approach to Covid-19 associated upper respiratory tract infection in Ayurveda: A review study - Gulab Chand Pamnani; Prabhakar Vardhan; Rajendra Kumar Soni (Wolters Kluwer Medknow Publications, 2020)
Introduction: The outbreak of COVID-19, a global pandemic is extraordinarily contagious, and its fast spread has affected more than 180 countries and has made the containment difficult. It is imperative to have proficient therapeutics to manage the current and upcoming situation. Unfortunately, no acceptable treatment protocol has been developed yet. On the other hand, a number of clinical entities have been described in detail with their treatment in Ayurvedic classics which closely resemble various presentations of COVID 19 infections. Material and Methods: A meticulous search of classic Ayurvedic texts, available contemporary literature pertaining to COVID 19 as well as clinical wisdom of stalwarts of Ayurveda was analysed to draw safe and effective treatment protocols as per presentation of the disease. Results and Discussion: Treatment protocols for COVID 19 with special reference to upper respiratory tract infections as detailed in Ayurveda have been developed and leads from these protocols can be utilized for the better management of COVID 19 related ailments and post COVID 19 complications.